2021
DOI: 10.3390/en14123441
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of Demand Response and Aggregators as a Solution to Optimize the Relation between Energy Producers and Consumers in order to Increase the Amount of Renewable Energy in the Grid

Abstract: Demand response plays a very important role in balancing the intermittent production of an increasing share of renewable energy sources on the energy market. This article analyses the importance of demand response and the role of aggregators for the new development of the electricity market, where the renewables will play a more important role. The main objective of this research is to determine the acceptance level of demand response and its implementation on the energy consumer side. This acceptance should i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Detailed results are presented in Figure 8. These results confirm the conclusions of the previous study [21]. Therefore, the consumers without experience in the energy field also agreed to their participation in DR programs in order to contribute to the reduction of CO2 emissions global warming.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Detailed results are presented in Figure 8. These results confirm the conclusions of the previous study [21]. Therefore, the consumers without experience in the energy field also agreed to their participation in DR programs in order to contribute to the reduction of CO2 emissions global warming.…”
Section: Resultssupporting
confidence: 90%
“…The residential consumer demand is distributed and heterogeneous; therefore, the implementation of DR programs is enabled due to the involvement of new service providers in electricity markets, such as aggregators [21]. Therefore, in order to promote sustainability in the future, energy sectors dominated by renewable DR solutions would play a more important role [16,22], but these have to be implemented through flexible contracts.…”
Section: Demand Response Flexible Contracts and Consumer Behavior In The Scientificmentioning
confidence: 99%
“…In [41], it is demonstrated that, independently from the adopted control strategy, the Aggregator performs a carbon dioxide emission reduction. In [38], the same result is achieved, and this influences the reputation of the Aggregator in the eyes of customers. Clients in fact express a positive attitude towards collaboration with the company to reach lower emissions, coherent with the current sensibility on climate issues.…”
mentioning
confidence: 59%
“…Forecasting capability is also a required skill for Aggregators, who must predict load, price, and generation. The same themes are faced in [38], where the main goal of the research is to define the optimal acceptance level of DR from consumers' perspective. In [46], the focus is instead on the remuneration tariff offered by the Aggregator to customers.…”
Section: Key Activities and Provided Servicesmentioning
confidence: 99%
See 1 more Smart Citation